Awareness to Consequences of Missing Teeth and Prosthodontic Treatment Modalities in Partially Dentate Patients Reporting for Dental Extraction (Medical Forum Monthly, 2023)
Objective: The main objective of the study is to find the awareness to consequences of missing teeth and prosthodontic treatment modalities in partially dentate patients reporting for dental extraction.Study Design: A prospective observational studyPlace and Duration of Study: This study was conducted at the Baqai Medical University Karachi from December 2022 to June 2023.Materials and Methods: This research employed a prospective observational study design to assess the awareness of consequences related to missing teeth and the knowledge of prosthodontic treatment options among partially dentate patients reporting for dental extraction.Results: Data was collected from 215 patients of both male and female patients. The mean age was 54.8 years, with a standard deviation of 6.2. The mean uric acid level was 8.5 mg/dL, with a standard deviation of 1.2. The study categorized patients based on age, gender, and education level to analyze their awareness regarding teeth problems. Age groups 31-40 and 41-50 showed higher awareness compared to other groups, and females exhibited relatively higher awareness. Out of 120 male patients, 85 were aware of treatment options, while 110 were aware of the consequences of missing teeth. Among 95 female patients, 70 were aware of treatment options, and 80 were aware of the consequences.Conclusion: It is concluded that this study highlights the importance of dental health awareness in patients with hyperuricemia and missing teeth. Tailored dental health education programs are essential to improve awareness and empower patients to make informed decisions about prosthodontic treatments.